2022
DOI: 10.1038/s41467-022-32879-9
|View full text |Cite
|
Sign up to set email alerts
|

A gene cluster in Ginkgo biloba encodes unique multifunctional cytochrome P450s that initiate ginkgolide biosynthesis

Abstract: The ginkgo tree (Ginkgo biloba) is considered a living fossil due to its 200 million year’s history under morphological stasis. Its resilience is partly attributed to its unique set of specialized metabolites, in particular, ginkgolides and bilobalide, which are chemically complex terpene trilactones. Here, we use a gene cluster-guided mining approach in combination with co-expression analysis to reveal the primary steps in ginkgolide biosynthesis. We show that five multifunctional cytochrome P450s with atypic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 61 publications
0
24
0
Order By: Relevance
“…The results showed that CYP450 had an important role in the oxidation, cyclization, and rearrangement of multi-step products, downstream of ginkgolides. The CYP450 enzyme is the first step in the oxidation reaction of levopimaradiene and ginkgolides [ 9 ]. In recent years, regarding WRKY , bZIP , bHLH, and the AP2 / ERF family, TFs have been continuously cloned, and they have been proven to have a key regulatory role in the biosynthesis of terpenoids [ 4 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that CYP450 had an important role in the oxidation, cyclization, and rearrangement of multi-step products, downstream of ginkgolides. The CYP450 enzyme is the first step in the oxidation reaction of levopimaradiene and ginkgolides [ 9 ]. In recent years, regarding WRKY , bZIP , bHLH, and the AP2 / ERF family, TFs have been continuously cloned, and they have been proven to have a key regulatory role in the biosynthesis of terpenoids [ 4 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…At present, it is believed that the biosynthesis of ginkgolide precursors mainly occurs through the MVA pathway, and the biosynthesis of the ginkgo diterpene lactone precursors mainly occur through the MEP pathway ( Figure 1 ) [ 6 ]. In the MEP pathway, DXS , DXR , HDR , LPS , CYP450, and other genes are considered to be the key enzyme genes regulating ginkgolide synthesis [ 7 , 8 , 9 ]. Most genes involved with the ginkgolide biosynthesis pathway have been cloned, among which, the more important genes are GbHMGR , GbDXS , GbDXR , GbHDR , GbGGPPS , GbFPS, and GbLPS .…”
Section: Introductionmentioning
confidence: 99%
“…Using a known transcript/gene (bait) to identify other transcripts/genes (prey) in the same pathway has proven an effective method to discover PNP pathway genes at the RNA level by gene co-expression analysis 28 or at the DNA or epigenomic level by clustered gene mining or co-regulation analysis 29,30 . Here, our work highlighted the possibility of a protein-level bait-prey approach to discover PNP pathways spatially organized in the form of dynamic enzyme complexes.…”
Section: Discussionmentioning
confidence: 99%
“…Over 30 BGCs have been identified in the past decade, [6,7] leading to the discovery of diverse pathways from plants, such as the opium poppy, [8,9] cucumber, [10] St John's wort, [11] and Ginkgo. [12] Post-translational regulation plays a crucial role in PNP biosynthesis, yet it has been less explored than other regulatory mechanisms. Specifically, the dynamic assembly of plant enzymes into enzyme complexes in planta is a protein-level cue that indicates the spatial organization of pathways but has been underutilized for pathway discovery.…”
Section: Introductionmentioning
confidence: 99%